Lactobacillus fermentum CRL1446 Ameliorates Oxidative and Metabolic Parameters by Increasing Intestinal Feruloyl Esterase Activity and Modulating Microbiota in Caloric-Restricted Mice - Russo, Matias Irineo; Fabersani Marrades, Mario Emanuel; Abeijon Mukdsi, Maria Claudia; Ross, Gloria Romina; Fontana, Cecilia Alejandra; Benítez Páez, Alfonso; Gauffin Cano, María Paola; Medina, Roxana Beatriz (2018)
The purpose of this study was to determine whether the administration of the feruloyl esterase (FE)-producing strain Lactobacillus fermentum CRL1446 enhances metabolic and oxidative parameters in caloric-restricted (CR) mice. Balb/c male mice were divided into ad libitum fed Group (ALF Group), CR diet Group (CR Group) and CR diet plus L. fermentum Group (CR-Lf Group). CR diet was administered during 45 days and CRL1446 strain was given in the dose of 108 cells/mL/day/mouse. FE activity was determined in intestinal mucosa and content at Day 1, 20 and 45. Triglyceride, total cholesterol, glucose, thiobarbituric acid reactive substances (TBARS) levels and glutathione reductase activity were determined in plasma. Gut microbiota was evaluated by high-throughput sequencing of 16S rRNA gene amplicons. At Day 45, total intestinal FE activity in CR-Lf Group was higher (p = 0.020) than in CR and ALF groups and an improvement in both metabolic (reductions in triglyceride (p = 0.0025), total cholesterol (p = 0.005) and glucose (p < 0.0001) levels) and oxidative (decrease of TBARS levels and increase of plasmatic glutathione reductase activity (p = 0.006)) parameters was observed, compared to ALF Group. CR diet increased abundance of Bacteroidetes and CRL1446 administration increased abundance of Bifidobacterium and Lactobacillus genus. L. fermentun CRL1446 exerted a bifidogenic effect under CR conditions.